TAN (F (?/2)) -expansion method for traveling wave solutions of AKNS and Burgers-like equations - Inan, Ibrahim E.; Duran, Serbay; Ugurlu, Yavuz (Elsevier Gmbh, Urban & Fischer Verlag, 2017)
In this paper, we implemented tan (F (xi/2)) -expansion method for the traveling wave solutions of the dissipative (2 + 1)-dimensional AKNS equation (Ablowitz-Kaup-Newell-Segur) and Burgers-like equations. We obtain triangular periodic solutions, multiple soliton-like solutions and rational for these equations. (C) 2017 Elsevier GmbH. All rights reserved.
Keywords: Dissipative (2+1)-dimensional AKNS equation; Burgers-like equation; Tan (F(xi/2))-expansion method; Traveling wave solutions